Comparative Analysis of Total Polyphenol Content in Olive Oil and Leaf Extracts from Frantoio and White Olive Cultivars in Libya - Estuty, Naser; Lazhari, Mohamed; Alsadi, Mustafa; Zayed, Zeinab; Algriany, Omran (AlQalam Journal of Medical and Applied Sciences, 2026)
This research has been done to compare the total phenolic content (TPC) of olive oil and olive leaf extracts obtained from two Libyan olive cultivars, Tarhuna White and Frantoio. Phenolics were measured by the Folin-Ciocalteu colorimetric assay, and the results were converted to gallic acid equivalents per kilogram of oil (mg GAE/kg) and per gram of dry leaf extract (mg GAE/g). The findings showed very significant differences between the TPC of the leaf extracts and their respective oils, with the leaf extracts from both cultivars being much higher. The leaf extract of the White olive had the highest TPC (2.35 mg GAE/g), and the Frantoio leaf extract came next (1.86 mg GAE/g). On the other hand, the oils had considerably lower phenolic contents, with the White oil containing 1.21 mg GAE/kg and the Frantoio oil 1.07 mg GAE/kg. The variations demonstrate the effect of different cultivar types on phenolic content, which might be due to different genes and enzymes involved in phenolic biosynthesis pathways. The results show that the choice of cultivar is not only important for olive oil quality but also for the recovery of phenolic compounds from the olive by-products. In general, olive leaves can be considered a good source of natural antioxidants for use in the nutraceutical industry. Further studies should be directed to chromatographic profiling of individual phenolic compounds, besides their evaluation These results demonstrate how cultivar selection affects phenolic content and point to olive leaves as a potential natural antioxidant source for nutraceutical uses. The development of value-added products from olive by-products should be supported by additional characterization of individual phenolic compounds and their bioactivity. Keywords: phenolic compounds; White olive oil; White olive leaves; Frantoio olive oil; Frantoio olive leaves